2018
DOI: 10.1093/infdis/jiy616
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Use of the Human Papillomavirus Vaccine on Recurrent Respiratory Papillomatosis: A Systematic Review and Meta-Analysis

Abstract: This updated and thorough review and meta-analyses supports the continued use of the HPV vaccine as an adjuvant treatment of RRP as significantly fewer surgeries per month are required after vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 49 publications
2
42
0
4
Order By: Relevance
“…Furthermore, available HPV vaccines are safe and tolerable [18–20] and a persistent cross-reactive immune response against HR-HPV not covered by the vaccine was shown in vaccinated women [21]. However, vaccination has a clinically relevant role also in subjects with established HPV infection [13, 22]. We analysed the HR-HPV patterns in HIV-positive MSM retained in care in a tertiary level hospital of a high-income country that provides free care and therapy, which is the best clinical scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, available HPV vaccines are safe and tolerable [18–20] and a persistent cross-reactive immune response against HR-HPV not covered by the vaccine was shown in vaccinated women [21]. However, vaccination has a clinically relevant role also in subjects with established HPV infection [13, 22]. We analysed the HR-HPV patterns in HIV-positive MSM retained in care in a tertiary level hospital of a high-income country that provides free care and therapy, which is the best clinical scenario.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis found a statistically significant reduction in the mean number of surgical procedures per month after HPV vaccination. 91 The proposed mechanisms of action include inhibition of latent HPV infection in the mucosa surrounding the surgical site by the antibody-mediated humoral immune response to the vaccine and activation of the cell-mediated response in the adaptive immune response by vaccination.…”
Section: Disease Coursementioning
confidence: 99%
“…The tetravalent vaccine acts targets HPV-6, HPV-11, HPV-16, HPV-18. A recent systematic review and meta-analysis found that the mean duration between surgeries in 63 juvenile and adult RRP patients significantly increased after HPV vaccination, from 7 to 34 months on average (25). The study found no significant differences by age of RRP onset (25).…”
Section: Hpv Vaccinementioning
confidence: 99%